Alternative methods and nature-based reagents for the reduction of graphene oxide: A review. (November 2015) - Thakur, Suman; Karak, Niranjan
Abstract: Reduction of graphene oxide (GO) using nature-based reagents and eco-friendly methods has attracted a great deal of scientific interest, with the focus ultimately on the production of graphene in bulk for its commercial applications. In this review, we highlight the recent advancements in environmentally benign processes and naturally existing reducing agents that have been used in the reduction of GO. This material is organized into two main categories: (i) nature-based reducing agents and (ii) eco-friendly approaches. The probable reduction mechanisms of GO by different reducing agents are discussed and critically evaluated. This review also covers the advantages and disadvantages of the various agents and techniques. Although a number of reducing agents and procedures are reported in the current literature, more research is still needed to develop optimal, environment-friendly strategies for the synthesis of GO.